A Development Strategy for the Northern Amazonian Border of Peru - Martinetti, Eduardo (2018)
In the context of the upcoming celebration of the twentieth anniversary of the Peruvian-Ecuadorian Peace Agreements of 1998, the article examines the performance of the Binational Plan for the Development of the Peru-Ecuador Border Region (Plan Binacional para el Desarrollo de la Región Fronteriza Perú-Ecuador) in compliance with its original investment program aimed at reversing underdevelopment conditions and raising the quality of life of the border population. Although the public financing made in the last two decades has beensubstantial, an overall assessment points to the persistence of important social, economic as well as social and productive infrastructure gaps within the Amazonian area of the Peruvian border, inhabited mainly by indigenous peoples.Based on this verification, the Peruvian Chapter of the Binational Plan (Capítulo Perú del Plan Binacional) has set out to restore institutional capacities envisaged in its mandate, as well as others recently established by Peruvian legislation, in order to strengthen its development-promoting and government management-articulation functions in the border area.To this end, it has drawn and is financing an integrated intervention strategy focused on five Amazonian river basins, while promoting at the same time the prioritization of public investments in social and productive infrastructure as well as the improvement of social services provided in the area, under interculturality and sustainability approaches.In order to overcome the welfare approach, the strategy proposes the development of skills and the gradual transformation of the productive base, in a friendly way with the natural environment, as an alternative to achieve the sustainable social development of the Amazonian border populations.